Ventilation, oxidative stress, and nitric oxide in hypobaric versus normobaric hypoxia - Faiss, Raphael; Pialoux, Vincent; Sartori, Claudio; Faes, Camille; Dériaz, Olivier; Millet, Grégoire P (Medicine and science in sports and exercise, 2013)
Slight differences in physiological responses and nitric oxide (NO) have been reported at rest between hypobaric hypoxia (HH) and normobaric hypoxia (NH) during short exposure.Our study reports NO and oxidative stress at rest and physiological responses during moderate exercise in HH versus NH. Ten subjects were randomly exposed for 24 h to HH (3000 m; FIO2, 20.9%; BP, 530 ± 6 mm Hg) or to NH (FIO2, 14.7%; BP, 720 ± 1 mm Hg). Before and every 8 h during the hypoxic exposures, pulse oxygen saturation (SpO2), HR, and gas exchanges were measured during a 6-min submaximal cycling exercise. At rest, the partial pressure of exhaled NO, blood nitrate and nitrite (NOx), plasma levels of oxidative stress, and pH levels were additionally measured. During exercise, minute ventilation was lower in HH compared with NH (-13% after 8 h, P < 0.05). End-tidal CO2 pressure was lower (P < 0.01) than PRE both in HH and NH but decreased less in HH than that in NH (-25% vs. -37%, P < 0.05).At rest, exhaled NO and NOx decreased in HH (-46% and -36% after 24 h, respectively, P < 0.05) whereas stable in NH. By contrast, oxidative stress was higher in HH than that in NH after 24 h (P < 0.05). The plasma pH level was stable in HH but increased in NH (P < 0.01). When compared with prenormoxic values, SpO2, HR, oxygen consumption, breathing frequency, and end-tidal O2 pressure showed similar changes in HH and NH. Lower ventilatory responses to a similar hypoxic stimulus during rest and exercise in HH versus NH were sustained for 24 h and associated with lower plasma pH level, exaggerated oxidative stress, and impaired NO bioavailability.